Chinese President’s Visit to Nepal and Consolidation of Relations of Two Countries - Dahal, Girdhari (Journal of Political Science, 2022)
This paper explores Chinese President Xi Jinping’s Nepal visit and its significance in diplomatic relations between the two countries. Drawing information from the secondary sources, this paper provides a brief overview and analysis of the Nepal-China relation, high-level visits between the two countries and Xi Jinping’s new diplomacy of Belt and Road Initiative (BRI). The paper argues that President Xi’s visit to Nepal on 13 October 2013 following his visit to India should be taken as part of his new diplomacy rather than the continuation of the tradition of exchanging high-level visits between the two countries. During this visit, Nepal and China signed a 20-point comprehensive agreement. In his statement, President Xi mentioned that China will help Nepal to get transformed from a ‘landlocked’ to a ‘land-linked’ country. For that purpose, he put forward the modality of Trans-Himalayan Multi-Dimensional Connectivity Network as a way out. Xi has expressed the commitment to opening up further new entry points between China and Nepal for enhancing connectivity between the two countries. President Xi announced financial help of around 56 billion rupees to Nepal between 2020 and 2022. The recent developments, with careful and timely implementation, have the potentiality of opening new geopolitical, regional, and economic opportunities for Nepal.